Starspot Mapping with Adaptive Parallel Tempering. II. Application to TESS Data for M-dwarf Flare Stars AU Microscopii, YZ Canis Minoris, and EV Lacertae - Kai Ikuta; Kosuke Namekata; Yuta Notsu; Hiroyuki Maehara; Soshi Okamoto; Satoshi Honda; Daisaku Nogami; Kazunari Shibata (The Astrophysical Journal, 2023)
Starspots and stellar flares are indicators of stellar magnetic activity. The magnetic energy stored around spots is thought to be the origin of flares, but the connection is not completely understood. To investigate the relation between spot locations deduced from light curves and the occurrence of flares therein, we perform starspot modeling for the TESS light curves of three M-dwarf flare stars, AU Mic, YZ CMi, and EV Lac, using the code implemented in Paper I. The code enables us to deduce multiple stellar/spot parameters by the adaptive parallel tempering algorithm efficiently. We find that flare occurrence frequency is not necessarily correlated with the rotation phases of the light curve for each star. The result of starspot modeling shows that any spot is always visible to the line of sight in all phases, and we suggest that this can be one of the reasons why there is no or low correlation between rotation phases and flare frequency. In addition, the amplitude and shape of the light curve for AU Mic and YZ CMi have varied in two years between different TESS cycles. The result of starspot modeling suggests that this can be explained by the variations of spot size and latitude.